Coping with stress in the workplace : an investigation of blue collar workers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Murray, Kristin (Massey University, 1994)
In recent years research on coping with job stress has begun to move away from investigation of the relationships between theoretical constructs and towards investigation of the constructs themselves. Such research includes the study by Dewe and Guest in which they presented an inductive approach to the development of a valid classification of the major methods of coping with work related stress built on a carefully articulated methodology. The present study replicated this methodology using a blue collar population. Comparisons were made between the present study and the results obtained by Dewe and Guest. Sex and ethnic differences were also investigated. Finally, the problem-focused, emotion-focused dichotomy was explored. Which was the most prevalent approach in the present population? One hundred and fifty three cleaners were given a self-report questionnaire consisting of both a coping measure and demographic information. Results indicated that five main coping strategies were used (Rational task oriented and preparation for dealing with the problem, Expression of emotion and avoidance, Attempts to tolerate or mitigate the effect, Distraction by pleasurable activities, and Emotional release). Despite the different work context, the present study showed consistencies with the previous studies. It appeared that four of the components were consistent across studies. These were direct action, emotional release, distraction, and passive rationalization. No sex differences in coping were found except in the use of prayer where it appeared that women used this strategy more frequently than males. No ethnic differences appeared to exist, that is, all ethnic groups used similar coping strategies. In contrast to previous findings, problem-focused coping was found to be the most prevalent form of coping among the present subjects. It is acknowledged that the cross sectional design, reliance on self report, and the characteristics of the questionnaire itself limit the conclusions to be drawn from the study. Future research should be undertaken on other populations, especially other blue collar workers with more restricted autonomy, thus counteracting some of the present study's limitations.
Keywords: Working class; Job stress; Psychology; New Zealand